A Comparative Study of Hypolipidemic Activities of the Extracts of Melissa officinalis and Berberis vulgaris in Rats - S Changizi Ashtiyani; A Zarei; S Taheri; A Rezaei; M Golshan; R Ghafarzadegan (Institue of Medicinal Plants, ACECR, 2013)
Background: Hyperlipidemia is a heterogeneous group of disorders characterized by an excess of lipids in the bloodstream Objective: Given previous studies on barberry and Melissa officinalis extracts, this study aims at comparing hypolipidemic activities of Melissa officinalis extract and Berberis vulgaris. Methods: For the purpose of this study, 64 Wistar rats were selected and divided into 8 groups (n=8). The control group was administered with ordinary diet the sham group was administered with high-fat diet and intraperitoneally 0.2 ml/dl of the extract solvent (normal saline) and similarly, experimental groups received minimal, moderate and maximum dosages of barberry and Melissa officinalis extracts. The treatment groupchr('39')s was given high-fat diet for 21 days. After this period, blood samples were taken and the gathered data were analyzed using SPSS software. Results: The amount of cholesterol, triglyceride and LDL were increased in the model group compared to the control group, whereas the same substances were decreased significantly in the group receiving the extract compared to the model group (p<0.05). Conclusion: Hypolipidemic properties of alcohol extracts of Melissa officinalis are more effective than those of Berberis vulgaris. Moreover, it should be noted that it is rather the antioxidant properties of Melissa officinalis and their effects on the increase in thyroid hormones as well as the presence of alkaloid compounds, such as berberine in Berberis vulgaris, that inhibits cholesterol synthesis and enables its excretion.